THE INFLUENCE OF MADDEN JULIAN OSCILLATION ON THE VARIABILITY OF PARTICULATE MATTER 2.5 CONCENTRATION IN INDONESIAN MARITIME CONTINENT - Ewila Br Sinuraya, Deta
Indonesia is the country that has the highest ranking in Southeast Asia in PM2.5 pollution. PM2.5 concentration can be decreased through various processes, one of which is wet deposition through the rain. Rainfall in Indonesia is affected by a very complex phenomenon, one of which is the Madden Julian Oscillation (MJO). MJO affects rainfall anomalies in the area it passes through. The increase and decrease of rainfall due to the MJO is thought to have influenced the distribution of PM2.5 in Indonesia. Previous studies have not discussed the effect of MJO on the variability of PM2.5 concentrations in all regions of Indonesia. Therefore, this research is conducted to study how MJO influences PM2.5 concentrations in the Indonesian Maritime Continent during the DJF and JJA seasons. The data used are surface PM2.5 concentration data from the reanalysis of MERRA-2 M2R1NXAER data, MSWEP rainfall data, and MJO data index from Bureau of Meteorology Australia for 1980-2018. The data was processed using composite analysis and correlation of rainfall anomaly and PM2.5 anomaly to see the effect of active MJO on PM2.5 concentration and its constituent components in the DJF and JJA seasons. The anomaly values of rainfall and PM2.5 were obtained by performing a bandpass filter with a cut-off of 20 and 70 days. Before doing a bandpass filter, the mean and first three harmonic of the annual cycle is removed to eliminate unwanted variability. The results of this study indicate that the PM2.5 concentration anomaly is higher in the JJA season than in the DJF season. In the DJF season, the PM2.5 concentration has a positive anomaly in phase 7 and a negative in phase 4 in most parts of Indonesia. In the JJA season, positive anomalies occur in phases 6-8 and negative anomalies in phases 1-4 in most northern Indonesia. PM2.5 anomaly responses due to rainfall anomalies in the DJF and JJA seasons mostly show a negative correlation in Indonesia, covering the areas of Kalimantan, Papua, Sumatra, and Sulawesi. The PM2.5 component, which has the most significant value during DJF and JJA when the MJO is active in Palangkaraya and Pekanbaru, is in the form of organic carbon, Jakarta is in the form of sea salt and SO4, and Mamuju does not show the presence of a dominant component of PM2.5.